Influence of Gender in Advanced Heart Failure Therapies and Outcome Following Transplantation - García-Cosío, María Dolores; González-Vilchez, Francisco; López-Vilella, Raquel; Barge-Caballero, Eduardo; Gómez Bueno, Manuel; Martínez-Selles, Manuel; María Arizón, Jose; Rangel Sousa, Diego; González-Costello, José; Mirabet, Sonia; Pérez-Villa, Félix; Molina, Beatriz Díaz; et al. (Frontiers in Cardiovascular Medicine, 2021)
Biological differences between males and females change the course of different diseases and affect therapeutic measures' responses. Heart failure is not an exception to these differences. Women account for a minority of patients on the waiting list for heart transplantation or other advanced heart failure therapies. The reason for this under-representation is unknown. Men have a worse cardiovascular risk profile and suffer more often from ischemic heart disease. Conversely, transplanted women are younger and more frequently have non-ischemic cardiac disorders. Women's poorer survival on the waiting list for heart transplantation has been previously described, but this trend has been corrected in recent years. The use of ventricular assist devices in women is progressively increasing, with comparable results than in men. The indication rate for a heart transplant in women (number of women on the waiting list for millions of habitants) has remained unchanged over the past 25 years. Long-term results of heart transplants are equal for both men and women. We have analyzed the data of a national registry of heart transplant patients to look for possible future directions for a more in-depth study of sex differences in this area. We have analyzed 1-year outcomes of heart transplant recipients. We found similar results in men and women and no sex-related interactions with any of the factors related to survival or differences in death causes between men and women. We should keep trying to approach sex differences in prospective studies to confirm if they deserve a different approach, which is not supported by current evidence.